Evaluation of “Kampus Mengajar”: an effort to increase participation at the University of Merdeka Malang - Dewi Izzatus Tsamroh; Widyarini Susilo Putri; Evi Rinata (University of Merdeka Malang, 2021)
“Kampus Mengajar” aimed to assist the process of teaching and learning at the elementary-junior high school level through technology adaptation, teaching numeracy and literacy, and administrative procedures. The deployment of students during the COVID-19 pandemic, which required learning to be conducted online, will significantly help the school, especially related to technology adaptation. However, this program was less attractive to students and lecturers at the University of Merdeka Malang; this was evident from the relatively small participation of students and lecturers at batch 1. In the initial observation, the “Kampus Mengajar” was less attractive because it did not follow the existing scientific competencies at the University of Merdeka Malang; thus, it was difficult to conduct a credit conversion process. This low participation affects the IKU ranking, where the University of Malang is in cluster 3 with 75.21. The purpose of this study was to evaluate the implementation of the “Kampus Mengajar” as an effort to increase the participation of the University of Merdeka Malang academic community. This research was conducted using an exploratory survey research method. Data were obtained through questionnaires and FGDs. The results showed that the implementation of the Kampus Mengajar at the University of Merdeka Malang had been running through socialization at the central level to the study programs. There was an increase in participation in each batch, both lecturers and students.